2010
DOI: 10.1097/wnr.0b013e32833774de
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic dynamics of musical emotion perception revealed by independent spectral components

Abstract: This study explores the electroencephalographic (EEG) correlates of emotional experience during music listening. Independent component analysis and analysis of variance were used to separate statistically independent spectral changes of the EEG in response to music-induced emotional processes. An independent brain process with equivalent dipole located in the fronto-central region exhibited distinct δ-band and θ-band power changes associated with self-reported emotional states. Specifically, the emotional vale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 23 publications
9
50
0
Order By: Relevance
“…In this study, the electrodes placed over the fronto-central region were relatively discriminative for most of subjects (c.f. Figure 6), which was in line with the previous studies (Altenmuller et al, 2002; Lin et al, 2010a). Over the brain region, the lateralized power asymmetry (in the left-right direction) well characterized the changes of emotional states, which may be supported by the role of the frontal cortical lateralization in emotion processing (Altenmuller et al, 2002; Allen et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the electrodes placed over the fronto-central region were relatively discriminative for most of subjects (c.f. Figure 6), which was in line with the previous studies (Altenmuller et al, 2002; Lin et al, 2010a). Over the brain region, the lateralized power asymmetry (in the left-right direction) well characterized the changes of emotional states, which may be supported by the role of the frontal cortical lateralization in emotion processing (Altenmuller et al, 2002; Allen et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Such variability may introduce the disparity of informative EEG patterns across individuals or subgroups (Lin et al, 2010a, 2011). To estimate the emotional states, it is plausible to expect a subject-specific classification model that well learned from an individual would have an optimal classification accuracy (Lin et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Another notable feature of our results is that a comparison of the shifts associated with the transfer of arousal and pleasantness (Figures 3b,d and 4b,d) clearly shows that the auditory-modulated arousal shifts outweigh the shifts in pleasantness. This may be interpreted as behavioral evidence for the dissociation of arousal and pleasantness in crossmodal emotional transfer, as earlier observed by electrophysiological studies on the unimodal processing of visual (Nielen et al, 2009) and musical (Lin et al, 2010) stimuli.…”
Section: Discussionmentioning
confidence: 81%
“…[61] Recent studies on musically induced feelings of pleasure and displeasure found an increase of fronto-medial theta activity with more positive valence. [56,57] For emotionally arousing stimuli, increases in theta band power have been reported over frontal [53,62] and parietal regions. [52] Similarly, a theta increase was also reported during anxious personal object rumination compared to non-anxious object rumination.…”
Section: Frequency-domain Correlatesmentioning
confidence: 99%
“…[52][53][54] The theta rhythm (4 to 8 Hz) has been observed during a number of cognitive processes, and its most prominent form, fronto-medial theta, is believed to originate from limbic and associated structures in the medial prefrontal cortex. [55][56][57][58] These theta oscillations subserve central executive function, integrating affective and cognitive sources of information, as necessary in working memory tasks [59,60] as well as in action monitoring. [58] Concerning affect, early reports mention an increasing 'hedonic' theta activity after interruption of pleasurable stimulation, but studies in children between 6 months and 6 years of age showed increases in theta activity upon exposure to pleasurable stimuli.…”
Section: Frequency-domain Correlatesmentioning
confidence: 99%